Photocatalytic degradation of phenol in a fluidized bed reactor utilizing immobilized TiO2 photocatalyst: Characterization and process studies - Zulfakar, Mokhtar (Asian Network for Scientific Information, 2011)
Link to publisher's homepage at http://www.ansinet.com/